Digitalizing metrology: The quality infrastructure services portal of IPEM-SP - Silva Robson; Oliveira Junior Marcos (EPJ Web of Conferences)
The digital transformation of Quality Infrastructure is one of the main challenges in the context of Industry 4.0. Not letting control be an obstacle to innovation is leading organizations to modernize and incorporate new practices and solutions. In Brazil, the Institute of Weights and Measures of the State of São Paulo (IPEM-SP) implemented a Quality Infrastructure innovation laboratory at the Technological Innovation Hub in the City of São José dos Campos. With the aim of bringing Quality Infrastructure closer to companies that promote innovation, enhancing products and services, IPEM-SP developed a Quality Infrastructure Services Portal (PSIQ) project, based on Artificial Intelligence, to provide initial assistance to those interested in learning about and using Quality Infrastructure tools. This Paper presents the PSIQ case study, a pilot project still under development.